176 Use of Computed Assisted Neuronavigation During Spine Fusions and Long-term Health Care Utilization: An Exact Matched Analysis of National Administrative Database. (April 2023) - Sharma, Mayur; Ugiliweneza, Beatrice; Boakye, Maxwell; Drazin, Doniel
Abstract : INTRODUCTION: Computer assisted neuronavigation (CAN) during spine fusions has increasing being utilized in the United States. The impact of CAN on long-term health care utilization is not well defined. METHODS: MarketScan database were queried using the ICD-9/10 and CPT 4th edition, from 2003 to 2019. We included patients ≥ 18 of age who underwent spine fusions with at least 2 years follow-up. Outcomes were repeat fusions or new fusions, length of stay (LOS), discharge disposition, hospital re-admissions, outpatient services, and medication refills for up to 24 months following the index procedure. RESULTS: Of 183, 620 patients who underwent spine fusions during the study years, 5046 (2.75%) were identified to have CAN used for the fusions. Exact matching was successful for 4861/5046 (96%) in the CAN group. CAN had no effect on LOS, home discharge, or complications at index hospitalization and 30-days post discharge. However, CAN was associated with a $7667 difference in median payments ($60501 vs $52834, p < .0001). CAN was associated with lower rates of repeat fusions at 6-months (3% vs. 4%), 12 months (2% vs. 3%) and 24 months (5% vs. 6%) following the index procedure, p < 0.05. Patients who underwent CAN had lower payments at 6 months ($5186 vs $5527, p: 0.0159), 12 months ($10267 vs $11262, p: 0.0207) and 24 months ($21453 vs $24355, p: 0.0021). CONCLUSIONS: CAN is increasing being used for spine fusions primarily for thoraco-lumbar procedures. No difference in complications, discharge disposition and LOS were noted across the cohorts at index hospitalization, with higher index payments with CAN use. CAN was associated with lower rates of repeat fusions and corresponding health care utilization for up-to 24 months following the index procedures compared to non-CAN cohort.